Modulatory effect of single nucleotide polymorphism in Xmn1, BCL11A and HBS1L-MYB loci on fetal hemoglobin levels in ? thalassemia major and Intermedia patients - Shabnam Bashir; Saqib Mahmood; Shahida Mohsin; Iqra Tabassum; Mahmood Ghafoor; Osheen Sajjad (Journal of the Pakistan Medical Association, 2021)
Objective: This study was aimed to evaluate the influence of these genetic modifiers (HBB gene cluster: rs7482144; BCL11A: rs766432; HBS1L-MYB: rs9399137) on the HbF levels in Thalassemia major and thalassemia intermedia. Methods: The cohort study comprised of 52 patients with <strong style="color: #202122; font-family: sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">?-thalassemia Intermedia and 64 patients of thalassemia major, all diagnosed in laboratories of Punjab thalassemia prevention program Hb-F was quantified by HPLC (Variant ll- Biorad). Primary mutation analysis and SNPS were done by ARMS PCR. SPSS version 20 i used for data analysis applying multivariate regression analysis. Results: The levels of Hb-F were primarily influenced by alleles of the HBG2, (rs7482144), and BCL11A (rs766432) gene but SNP of HBS1L-MYB (rs9399137) has no significant role. The rs7482144 SNP explained 8.3% of the variation in the Hb-F levels, while 5% of trait variation was explained by rs766432. Conclusion: There is clear association between Hb-F level and SNPs in HBG2, (rs7482144), and BCL11A (rs766432) gene. This correlation is additive and seen both in thalassemia major and thalassemia Intermedia cohorts, more so in case of later. Continuous...